Ant Colony Optimization of feeder bus routes for electric train service - Azam, S.F.M. (Institute of Electrical and Electronics Engineers Inc., 2015)
The Electric Train Service (ETS) was introduced as a faster, safer, greener and more reliable mode of public transportation between the major cities of Ipoh and Kuala Lumpur. This service holds great potential in benefitting the society and the nation. A significant issue which affects the effectiveness of the ETS however, is the absence of an efficient feeder bus system. This paper presents a research to design a efficient and effective feeder bus route using the Ant Colony Optimization (ACO) technique. The objective function is designed such that the optimized route should provide the broadest service coverage, highest operation profit, shortest total travel time, and meet the highest demand. For the intents and purposes of this research, the Ipoh, Perak ETS station has been selected as a case study. The results obtained from simulations show that solving the route optimization problem using ACO can yield a wide coverage route which provides highly efficient and effective feeder bus service. Â© 2015 IEEE.